2021
DOI: 10.1111/famp.12641
|View full text |Cite
|
Sign up to set email alerts
|

Family Resilience in a Resource‐Cursed Community Dependent on the Oil and Gas Industry

Abstract: The economic and social well‐being of rural, “resource‐cursed” communities can depend on the boom‐bust cycles of a single industry like oil and gas. This study used a constructivist, inductive approach to identify the challenges placed on families in one such community and the processes that strengthen family resilience. Semi‐structured interviews were conducted with 35 adult residents (30–76 years old, 19 women) from a community in Alberta, Canada, that has specialized in oil and gas extraction for 70 years a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The most analysed perspective in the literature on the work-family relationship has been the negative one, whose core concept is work-family conflict. In their study, Greenhaus and Beutell [4] highlight three types of conflict or relationship; transposing it to this research, they identified the following: (i) the first, temporal-based, arises from the time required to perform one role interfering with the time available to perform another, reducing said role [46,93,94]; (ii) the second refers to pressure conflicts and is based on the conception that the pressure caused in one domain will affect the other domain [35,41,44] and, (iii) the third refers to the type of behavioral conflict that concerns the incompatibility of behaviors expected in each of the roles [33,39,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most analysed perspective in the literature on the work-family relationship has been the negative one, whose core concept is work-family conflict. In their study, Greenhaus and Beutell [4] highlight three types of conflict or relationship; transposing it to this research, they identified the following: (i) the first, temporal-based, arises from the time required to perform one role interfering with the time available to perform another, reducing said role [46,93,94]; (ii) the second refers to pressure conflicts and is based on the conception that the pressure caused in one domain will affect the other domain [35,41,44] and, (iii) the third refers to the type of behavioral conflict that concerns the incompatibility of behaviors expected in each of the roles [33,39,43].…”
Section: Discussionmentioning
confidence: 99%
“…For the authors Jones et al [38], there is an urgent need for institutional leaders to implement programs that can promote awareness and normalization of caregiving challenges, in addition to providing funding and other tangible resources to reinforce a broader culture that affirms the presence of work-family relationship challenges. The study by Höltge et al [39] addresses the economic and social well-being experiences of communities that depend on the boom-and-bust cycles of a single industry, such as oil and gas. The results point out that many families experienced a never-ending cycle of work-life balance and income instability throughout the economic cycle.…”
Section: Quant Of Articles Author (Year)mentioning
confidence: 99%
See 1 more Smart Citation
“…Decades of research on adversity in families illuminate their capacities for resilience in varied contexts, cultures, and family forms, including during normative experiences in the family life cycle, in the face of loss and bereavement, collective trauma, serious illness and disabilities, and in multistressed families (Walsh, 2015(Walsh, , 2023. For instance, in a rural "resource-cursed" community that has longstanding economic instability, families demonstrated key elements of resilience including flexibility in family routines and roles as well as acceptance of economic volatility (Höltge et al, 2021). Adaptive family processes are evident in families with incarcerated parents, wherein children, youth, and families cope with the challenges of having an incarcerated parent in adaptive and varied ways, including continued contact and closeness with incarcerated parents and strengthened parent-child relationships with the parent who is not incarcerated (Arditti & Johnson, 2022).…”
Section: What Is Family Resilience?mentioning
confidence: 99%
“…One of the most extensively applied frameworks is the Walsh's ( 6 ) family resilience clinical practice framework, which outlines three important domains of family resilience: family belief systems, organizational processes, and communication processes, which made understanding family resilience feasible. Moreover, an increasingly important area of family care practice is identifying, strengthening, and promoting family resilience ( 9 , 10 ). However, empirical studies on family resilience of stroke survivors and its predictors are limited, which is not in favor of targeted interventions for the families of post-stroke patients.…”
Section: Introductionmentioning
confidence: 99%